Design and Analysis of Enterprise Management System Framework Based on Blockchain Technology. Issue 2 (April 2021) - Jiang, Leilei; Dong, Ke
Abstract: With the advent of the data age and the rapid development of Internet of things technology, blockchain technology has been proposed. Since the advent of blockchain, it has been widely concerned. Its tamper proof, traceability, anonymity and openness have attracted more and more people's interest. Many researchers and practitioners have stepped into this field. In this paper, the related technical concepts of blockchain are described, and the blockchain technology is integrated into enterprise management innovation to provide new ideas for enterprise management. This paper designs an enterprise management system based on blockchain technology according to the requirements, and carries out bug monitoring and pressure test on the system, and the results show that the system can be used well.